2020
DOI: 10.1021/acssuschemeng.0c01222
|View full text |Cite
|
Sign up to set email alerts
|

CO2-Binding Organic Liquids Comprised of 1,1,3,3-Tetramethylguanidine and Alkanol for Postcombustion CO2 Capture: Water Inhibitory Effect of Amine Promoters

Abstract: CO 2 -binding organic liquids (CO 2 -BOLs) are switchable polarity solvents that can be used as nonaqueous green solvents for energy-efficient CO 2 capture. In this study, the novel three-component CO 2 -BOLs comprised of 1,1,3,3-tetramethylguanidine (TMG) as a superbase, an alkanol (methanol, nbutanol, sec-butanol, and 1-hexanol), and an amine (EEA, MEA, AMP, DEA, AEEA, PZ, TETA, and DETA) were introduced. Screening experiments were performed to find the best combination of solvent components based on CO 2 lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…However, several limitations have been detected. Application of some amines led to the formation of solid products, which is detrimental for practical applications [131]. Alkanolguanidines show an exponential viscosity increase at increasing CO 2 loadings (up to 103 cP at full loading); the only way to maintain the control of viscosity is to operate with limited CO 2 loadings.…”
Section: Co 2 -Binding Organic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several limitations have been detected. Application of some amines led to the formation of solid products, which is detrimental for practical applications [131]. Alkanolguanidines show an exponential viscosity increase at increasing CO 2 loadings (up to 103 cP at full loading); the only way to maintain the control of viscosity is to operate with limited CO 2 loadings.…”
Section: Co 2 -Binding Organic Liquidsmentioning
confidence: 99%
“…Recently, CO 2 -BOLs made up of 1,1,3,3-tetramethylguanidine (TMG) as a superbase, an alkanol (methanol, n-butanol, sec-butanol, and 1-hexanol), and an amine (EEA, MEA, AMP, DEA, AEEA, PZ, TETA and DETA) were characterized in terms of absorption rate and CO 2 loading [131]. The results show that, owing to the addition of MEA, the ternary CO 2 -BOL made up of methanol-TMG and MEA does not form any bicarbonate salt, which limits the regeneration efficiency and the solvent applicability.…”
Section: Co 2 -Binding Organic Liquidsmentioning
confidence: 99%
“…Recently, Zhang et al 36 found that all parts of 1,5‐Diazabicyclo[4.3.0]non‐5‐ene (DBN)‐BmimCl‐Im have a synergistic effect, and the protonated superbase plays a key role in absorption. Hedayati Ali et al 37 reported the organic liquids combined with CO 2 are non‐aqueous green solvents for CO 2 capture, and 1,1,3,3‐tetramethylguanidine (TMG)/methanol/monoethanolamine (MEA) binding organic liquid (BOL) was selected as the best solvent. In addition, Zhu et al 13 proved that DBU as a cation has excellent CO 2 capture and recycling capacity.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 Various methods have been proposed to capture CO 2 , such as solid adsorption, 5 , 6 membrane separation, 7 , 8 and organic solvent scrubbing. 9 11 The organic solvent scrubbing method involves either physical or chemical solvents according to the strength of the solvent–solute interaction. Representative amine scrubbing is the most commonly used commercial technology for CO 2 capture through chemical absorption.…”
Section: Introductionmentioning
confidence: 99%
“…The extensive use of fossil fuels and the rapid increase of CO 2 content in the atmosphere have caused the greenhouse effect and the negative consequences of global climate changes, and this has attracted widespread attention. , Experts generally deem CO 2 capture and utilization (CCU) to be one of the most effective methods to reduce global CO 2 emissions. , Various methods have been proposed to capture CO 2 , such as solid adsorption, , membrane separation, , and organic solvent scrubbing. The organic solvent scrubbing method involves either physical or chemical solvents according to the strength of the solvent–solute interaction. Representative amine scrubbing is the most commonly used commercial technology for CO 2 capture through chemical absorption. , However, the loss of amine by volatilization easily causes secondary pollution in the process of CO 2 removal.…”
Section: Introductionmentioning
confidence: 99%